Domestication and uses of the dog in western Europe from the Paleolithic to the Iron Age. (1st July 2014) - Horard-Herbin, Marie-Pierre; Tresset, Anne; Vigne, Jean-Denis
Abstract: This paper reviews the knowledge of the history of the dog in western Europe acquired through archaeozoology. The first part examines the question of domestication of the wolf during the Upper Paleolithic, by highlighting the sometimes contradictory archeological and genetic findings. It also briefly lays out the different controversies regarding the site or sites of domestication of the dog in the world and the presumed dates of this major phenomenon in human history. The second part deals with the evolution of canine morphology from the Paleolithic to the Iron Age, integrating, for example, the latest discoveries regarding domestic coat colors in the Mesolithic. Finally, the presumed and attested uses of dogs throughout European pre- and protohistory are presented, including certain practices that lasted over time.